PENGARUH METODE SURVEY-QUESTION-READ-RECITED-REVIEW (SQ3R) TERHADAP KETERAMPILAN BERPIKIR KRITIS SISWA PADA SUB MATERI SISTEM EKSKRESI MANUSIA - Julia, Dede; Hartati, Sri (Jurnal BIOEDUIN, 2015)
The purpose of this study is to describe the feasibility SQ3R method on the material sub human excretory system, analyzing the critical thinking skills of students in the submaterial human excretory system using SQ3R method, analyzing the critical thinking skills of students in the sub-material human excretory system with conventional learning, analyzing the effect of the method SQ3R to the critical thinking skills of students in the sub-material human excretory system and describes the students' response to the use of SQ3R method in sub-material human excretory system. This study departs from the idea that learning the material sub human excretory system using the method SQ3R can help students to better concentrate on the text they have read and make students use thinking skills in understanding the main ideas / concepts in the text. Such learning can train students to develop critical thinking skills. The research method used is the method of quasi-experimental research design with non-equivalent control group design. Samples were taken as much as two classes with saturated sampling techniques. The instrument used is the observation sheet, questionnaire, pretest and posttest form of description as much as 10 questions that have previously been tested. The results obtained the critical thinking skills of students in the experimental class 70.32 and N-gain of 0.28 with the qualification being. Meanwhile, critical thinking skills of students in the control classes 64,35 and N-gain of 0.28 with low qualifications. Results of Mann-Whitney test on the N-gain obtained Z hitung 6.71 > 1.65 Z tabel thus Ho is rejected and Ha accepted. It is proved that there are significant SQ3R strategy on students' critical thinking skills in the sub-material human excretory system. This is supported by the average percentage of adherence to activity by 90% of teachers with excellent qualifications, and the percentage of student responses by 71% with strong qualifications.